2019
DOI: 10.3389/fpsyg.2019.02456
|View full text |Cite
|
Sign up to set email alerts
|

Caring for Oneself or for Others? How Consistent and Inconsistent Profiles of Health-Oriented Leadership Are Related to Follower Strain and Health

Abstract: Health-oriented leadership consists of three dimensions that contribute to employee health: staff care, i.e., health-specific follower-directed leadership, as well as both leaders’ and followers’ self care, i.e., health-specific self-leadership. This study explores profiles of follower self care, leader self care and staff care, and investigates the relationships with follower health in two samples. We identified four patterns of health-oriented leadership: A consistently positive profile (high care), a consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 70 publications
(158 reference statements)
5
76
1
3
Order By: Relevance
“…Beyond that, the present study was able to ascertain further health-oriented self-leadership behavior: sleep, recreational activities, time management, and mental handling of stress. Previous empirical studies on the HoL model showed that leaders serve as role models for employees’ self-leadership and thus indirectly influence employees’ health [ 62 , 70 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Beyond that, the present study was able to ascertain further health-oriented self-leadership behavior: sleep, recreational activities, time management, and mental handling of stress. Previous empirical studies on the HoL model showed that leaders serve as role models for employees’ self-leadership and thus indirectly influence employees’ health [ 62 , 70 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, leaders play a crucial role in workplace health prevention due to their role model function and evident influence on employee health [ 45 , 61 , 62 ]. A current meta-analysis emphasizes the relevance of leader’s well-being for the entire organization, as it affects leadership behavior and consequently the well-being and performance of employees [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Welchen entscheidenden Einfluss die Kombination aller drei Komponenten des HoL-Ansatzes (StaffCare, SelfCare der Führungskräfte und Mitarbeitenden) auf die Gesundheit der Mitarbeitenden haben können, konnten Klug et al [20] nachweisen. Sie konnten erstmalig anhand des HoL-Ansatzes vier Profile gesundheitsorientierter Führung identifizieren und diese auch im Zusammenhang mit Gesundheitsparametern untersuchen.…”
Section: Definition Des Hol-ansatzesunclassified